The library's legal answer book - Minow, Mary (American Library Association, 2003)
Publisher's description: Libraries are in the thick of legal issues as new technologies add layers of complexity to everyday work in the library. How do you know what's legal? What can you do to identify and address issues before they turn into bona fide legal matters? Where do you turn for help? With coverage of all the issues of the day--filters, fair use, copyright, Web publishing and Internet use, software sharing, ADA compliance, free speech, privacy, access, and employment and liability issues--you will have a "librarian's J.D." in short order! Detailed and ready-to-apply answers to more than 600 legal questions will make this trouble-shooting guide your favorite quick-reference.